Genetic testing enhances diagnosis in critically ill neonates: insights from the first Colombian cohort - Rueda-Gaitán, Paula; Rodríguez Gutiérrez, Diego Alejandro; Sanchez Rubio, Yuri Natalia; Carrillo, Yina D.; Martínez de la Barrera, Leslie Ivonne; Muñetones Reina, Néstor Nenroth; Isaza-Ruget, Mario; López Rivera, Juan Javier (Frontiers in Pediatrics, 2025)
IntroductionThe integration of genetic testing in pediatrics has advanced significantly in recent years. The incorporation of technologies such as Next Generation Sequencing (NGS) and array-based Comparative Genomic Hybridization (aCGH) in increasingly younger patients has accelerated the transition toward precision medicine.MethodsThis retrospective cross-sectional study (January 2021–June 2024) included 187 neonates (≤90 days old) from the NICUs of the Clínica Colsanitas network in Bogotá, Colombia and evaluate the diagnostic yield for genomic testing comprising 82 Whole Exome Sequencing (WES) and 125 aCGH tests, with 18 patients undergoing both. This study also examined the phenotypic traits of patients to investigate potential associations with a higher diagnostic yield. Symptoms were characterized using Human Phenotype Ontology (HPO) terms and analyzed with a propagation algorithm for improved accuracy.ResultsThe diagnostic yield was 30.5% for WES and 8% for aCGH. Noteworthy, we identify four novel SNVs with potential pathogenicity and report a rare case of co-occurring deletion and duplication, both previously unreported in the literature. Phenotypic analysis revealed a strong association between what were considered “growth abnormalities” related to intrauterine growth restriction, low birth weight, and/or growth retardation, with “head or neck abnormalities” related to specific malformations of the face or head and/or dysmorphic facial phenotypes.DiscussionThese findings highlight the importance of applying, in particular, WES as a first-level clinical diagnostic test in patients with suspected genetic or complex diseases who are hospitalized in the NICU. Consequently, it is hoped that these results will support the development of clinical guidelines for the integration of molecular genetic testing into neonatal care in Colombia.